ANALYSIS OF THE COMPOSITION OF GASES IN THE SYNTHESIS OF CALCIUM CYANAMIDE (Academia Science Repository, 2023)
Technical solutions have been developed to create a technology for the production of calcium cyanamide from lime, carbonate anhydride and industrial ammonia. A technological scheme for the production of nitrogen fertilizer and an effective defoliant - calcium cyanamide has been developed and the optimal technological parameters of the process have been determined at the experimental plant. An experimental batch of calcium cyanamide has been produced.